Lifelong learning programs in Malaysia - Ab Hamid, Kamal; Mustaffa, Jamaludin; Ahmad, Za'im; Othman, Zaheruddin; Hamzah, Mohd Hilmi; Don, Mohd Sobri; Abdul Rahman, Hamzah (2010)
21st Century marks the new mindset on lifelong learning where international society is more receptive to the idea of increasing knowledge and skills through lifelong learning programs.Realizing that the role of lifelong learning is very important in ensuring the country’s wealth and prosperity, many governments, including Malaysia have taken proactive actions to promote lifelong learning initiatives. Malaysian government has enacted policies with lifelong learning as a main tenet in the nation’s development planning. For instance, Third Outline Perspective Plan (OPP3) 2001 – 2010 and 8, 9, and 10 Malaysia Plans - long-term development plans of the national framework in facing globalization challenges, economic liberalization and economic environment – were formulated. The focus of this research is to discuss issues pertaining to lifelong learning in Malaysia. Specifically, this research aimed to discuss lifelong learning programs that are offered by institutions and employers, and examined the benefits of the programs.